Main measures of youth sports organization and development on table tennis - Zhong, Y.; Zhang, B.; Guo, Q. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
Reserve talents are the foundation of a sports project maintaining enduring, while youth table tennis organizations at all levels is the important carrier of table tennis development, the basic support of table tennis reserve personnel training and the vital guarantee of forming a system of training table tennis reserve personnel scientifically and effectively. The aim of this essay is to provide reference for relevant departments in order to promote a healthy and orderly development of table tennis reserve personnel training, to make the table tennis competitive level of our country lead the world in the long term and the table tennis movement in schools as well as among the masses develop vigorously so that it can bring into full play the social value in the process of constructing a harmonious society. Research methods such as document literature, expert interviews and logical analysis will be carried out in this essay to discuss the main measures of youth sports organization and development on table tennis projects. It is considered that the main measures are as follows: 1. to strengthen management of organizations and promote three-in-one harmonious all-round development of "group, competition, learning" of table tennis in China. 2. to consolidate foundation, improve youth table tennis sports organization service network, train table tennis reserve personnel in multi-channels. 3. to enhance institutional construction and intensify standardized management. 4. to deepen reform and transform functions, to reinforce construction of associations, to accelerate process of association substantiation. 5. to strengthen propaganda and create atmosphere. 6. to unearth table tennis cultural connotation deeply and increase influence of table tennis sports by using the power of culture. 7. to improve communication of departments and promote the win-win situation of training talented people of physical and cultural dual-system. In short we must keep pace with the times and explore in depth, enhance youth table tennis organization and construction to be suitable to actual circumstances, fully guarantee a scientific and effective personal training system. In the meanwhile, we must improve communication between physical and cultural education departments and promote the win-win situation of training talented people of physical and cultural dual-system to achieve a healthy and sustainable development of reserve personnel cultivation.